Image 3_Post-traumatic stress disorder in French Guiana: prevalence and risk factors in the general population.png - Mathieu Nacher (340458) (2025)
Background The context of French Guiana—characterized by frequent violence and intense immigration from regions where traumatic events are common—may lead to a different epidemiology of post-traumatic stress disorder (PTSD) compared with mainland France. In the absence of prior data, we aimed to estimate the overall prevalence of PTSD in the general population of French Guiana, along with its prevalence across different sociodemographic groups. Methods A cross-sectional survey was conducted between March and August 2021, interviewing 881 subjects aged >17 years. Results The overall prevalence of PTSD was 7.6 [95%CI = 5.9–9.5]. After adjusting for potential confounders among sociodemographic variables, only female sex (adjusted prevalence ratio (aPR) = 2.1, 95%CI = 1.2–3.6, p = 0.006), being a student (aPR = 2.4, 95%CI = 1.0–5.6, p = 0.05), being from Suriname (aPR = 5.8, 95%CI = 1.0–33.4, p = 0.05), not having completed primary education (aPR = 3.4, 95%CI = 1.3–8.9, p = 0.01), and being separated or divorced (aPR = 3, 95%CI = 1.1–8.2, p = 0.02) were significantly associated with PTSD. Of the 67 individuals with PTSD (46.3%), 31 sought care, 21 (31.3%) reported having received treatment for their symptoms, and 29 (43.3%) reported using alternative treatments, mostly plant-based traditional medicine. Of the 394 individuals who had experienced an unusual traumatic event, 67 (17%) developed PTSD. Conclusion We found that the prevalence of PTSD is approximately 10 times higher than in mainland France and that substantial differences exist across origin, gender, and age group. We also observed that the majority of individuals do not seek treatment for their symptoms, and those who do often combine Western and traditional medicine. These findings emphasize the need for culturally sensitive approaches to screening and care.